Asymmetric total synthesis of smyrindiol employing an organocatalytic aldol key step - Enders, Dieter; Fronert, Jeanne; Bisschops, Tom; Boeck, Florian (Beilstein Journal of Organic Chemistry, 2012)
The first organocatalytic asymmetric synthesis of smyrindiol, by using an (S)-proline catalyzed enantioselective intramolecular aldol reaction as the key step, is described. Smyrindiol was synthesized from commercially available 2,4-dihydroxybenzaldehyde in 15 steps, with excellent stereoselectivity (de = 99%, ee = 99%). In the course of this total synthesis a new and mild coumarin assembly was developed.
Keywords: aldol reaction; asymmetric synthesis; organocatalysis; proline; smyrindiol